Pertanggungjawaban Notaris Dalam Pembuatan Waarmerking Surat Di Bawah Tangan - Yusa Putri, Ni Nyoman Ivy Indira; Darmadi, A.A. Ngurah Oka Yudistira (Acta Comitas; Vol 10 No 01 (2025)DO - 10.24843/AC.2025.v10.i01.p6, 2025)
The purpose of this study is to determine and analyze the evidentiary power of a private agreement consulted by a Notary and the notary's responsibility for a private letter that is recorded by registering it in a special book reviewed from the Notary Law. This legal research is a normative legal research in which a review of applicable laws and regulations is carried out and secondary data is used as the main data. Based on the results of the study, it can be concluded that: (1) Article 15 paragraph (2) letter b of the UUJN in its implementation has not been implemented optimally because many people still do not understand that a Notary is not authorized to help prepare a private letter that is in the warmeking; and (2) Responsibility for a private letter whose preparation is assisted by a Notary and in the warmeking, namely the Notary cannot be held accountable either personally or in his position.